THE HARDSHIP OF CLUSTERS’ FORMATION AT RUSSIA - S.G. Vazhenin; V.V. Sookhikh (Экономика региона, 2009)
The article is devoted to the hardship of clusters give an example Moscow cluster of textile industry.